EXPLORATION OF INPUT FACTORS IN HIV/AIDS COUNSELING AT THE TELADAN HEALTH CENTER IN MEDAN CITY - Hasibuan, Rapotan (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
HIV cases in Indonesia peaked in 2019 at 50,282 cases, 64.50% of which were male. In addition, the proportion of AIDS patients at 68.60% was also male. A number of input factors in HIV/AIDS counseling should be expected to contribute to the success of reducing the transmission rate of the disease. This study aims to explore the input factors of HIV/AIDS counseling at Puskesmas Teladan Medan including counseling officers (man), counseling costs (money), facilities (machine), materials (material), methods (method) and implementation time (time). This research is a qualitative research with descriptive approach with phenomenological design. The research was conducted for two months involving 7 (seven) informants purposively consisting of 3 (three) HIV/AIDS program managers of Puskesmas, 1 (one) HIV/AIDS disease prevention and control program section of Medan City Health Office and 3 (three) patients with HIV/AIDS. Data collection was conducted with in-depth interviews, observation, and documentation studies. The questions asked contained informant characteristics, human resources (man), funds (money), methods (methode), facilities (machine), materials, and time (time). This study found the low quantity of counseling officers and not in accordance with the SOP. In addition, the source of funding for activities in organizing the VCT clinic is inadequate and the material is only presented in the form of lectures without using any media. The dominant counseling method used is individual counseling where there is no routine service schedule and timing when conducting counseling.